Listing of Professional Vocational Teacher Education Modules - Ohio State Univ., Columbus. Center for Vocational Education; Ohio State Univ., Columbus. Center for Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This document contains a list of vocational teacher education modules. The modules are grouped into ten categories as follows: (1) program planning, development, and evaluation; (2) instructional planning; (3) instructional execution; (4) instructional evaluation; (5) instructional management; (6) guidance; (7) school community relations; (8) student vocational organization; (9) professional role and development; and (10) coordination. Titles of the modules are included in each category, along with the identification numbers of the performance elements which form the basis of each module. (JD)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Competency Based Teacher Education; Inservice Teacher Education; Learning Modules; Preservice Teacher Education; Teacher Education; Vocational Education; Reference Materials, Bibliographies